The Semantic and Syntactic Evolution of Conjunctions in French: The Case of ains - Niewzorowa, Swietłana (Taikomoji kalbotyra, 2021)
The present study is part of the current of diachronic research on conjunctions. All linguists confirm that in Old French two opposing conjunctions were used: ains / mais. However, in modern French, only one contrast conjunction provides an opposing connection, namely mais. The reasons for the rapid decline of the ains conjunction are not clear, and the time of its disappearance is not precise. In this article, the author focuses on the semantic analysis of ains from Old French until the 17th century, i.e. until the time where this conjunction passed into archaism and when the Academy declared: “it is old” (Dictionary of the French Academy 1694). The study deals with the specific syntactic uses of the conjunction in question in various literary texts. By referring to descriptive, semantic and functional analyses, it is possible to identify specific features of the ains conjunction, as well as to reveal the conditions under which its disappearance took place. The study is also trying to answer the question why this Old French conjunction, very common in the past, disappeared.